Microscopic calculation of delayed-photoneutron production in D2O using Geant4. (July 2019) - Rand, E.T.; Atfield, J.E.; Yaraskavitch, L.R.
Highlights: Simulated photoneutron data for the thermal fission of U-233, -235, and Pu-239. Large discrepancies comparing simulated yields to the recommended yields for U-235. We show that the recommended yields are inconsistent with the recent nuclear data. First time photoneutron group sets have been derived for isotopes U-233 and Pu-239. Abstract: In this work we apply the Geant4 toolkit and recent fission yield data to calculate the photoneutron yield from the thermal fission of 233, 235 U and 239 Pu within a quasi-infinite bath of D2 O. The simulation results were fit to a series of exponential terms enabling a direct comparison to historical "11 group" photoneutron data and the application for use in kinetics analyses. Large discrepancies were observed comparing the simulation results to the recommended 235 U photoneutron yields (Laughton, 1998) within the shortest (<100 s) and longest (>10 5  s) half-life groups. These results raise concerns on the validity of the yields derived from experimental data. A detailed discussion on the origin of the historical data is presented as well as explanations for the observed disagreement.